2018
DOI: 10.1007/s11284-018-1587-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of waterbirds wintering in Douz wetlands (south Tunisia): factors affecting wetland occupancy and species richness

Abstract: Understanding the environmental factors shaping wetland attractiveness for waterbirds is an important question in wetland ecology and for conservation purposes. However, detailed data from numerous North African wetlands, notably those situated in inland areas, are still lacking. Thus, the aim of this study was to identify the factors influencing wetland use by waterbirds wintering in one of such poorly known habitat systems, namely the Saharan wetland complex of Douz, in south‐western Tunisia. Thirty‐four wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In the Northern slope of the Mediterranean, our results are very close to those cited in Kavala (Greece) and in Rovaniemi (Finland) with 26 and 15 breeding species, respectively. However, the recorded breeding birds are inferior when compared to other Moroccan ecosystems counting farmlands that host nearly 60 breeding birds [36], forests with 70 breeding species [22,24,47], and wetlands with nearly 100 breeding species [14]. Te increased urbanization rate is suggested to be behind this lower avian diversity in Fez city.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the Northern slope of the Mediterranean, our results are very close to those cited in Kavala (Greece) and in Rovaniemi (Finland) with 26 and 15 breeding species, respectively. However, the recorded breeding birds are inferior when compared to other Moroccan ecosystems counting farmlands that host nearly 60 breeding birds [36], forests with 70 breeding species [22,24,47], and wetlands with nearly 100 breeding species [14]. Te increased urbanization rate is suggested to be behind this lower avian diversity in Fez city.…”
Section: Discussionmentioning
confidence: 89%
“…Nests of birds of prey Falco tinnunculus and Accipiter nisus were built separately in urban forests far from the breeding passerines. Te segregation of breeding habitats between predators and preys is currently cited among avian species [56,57] as in the case of olive orchards surrounding Fez city [18] in which the breeding Doves (Streptopelia decaocto and Streptopelia turtur) nested far from the predatory Maghreb magpie (Pica mauritanica) and the case of Oued Bouhellou watershed in which the community of breeding passerines selected nesting sites far from the birds of prey counting Falco tinnunculus, Falco naumanni, Buteo rufnus, Circus aeruginosus, Elanus caeruleus, Lanius excubitor, and Lanius senator [47]. In the same way, our study revealed a clear habitat partitioning between Streptopelia decaocto that nested in urban farmlands and its competitor Spilopelia senegalensis concentrated in green gardens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wetland depth is very essential for sustaining different species (Lantz et al, 2011;Hamza and Selmi, 2018). Depth is a hydro-ecological aspect whose variation is linked to the species richness, diversity, comfortability, particularly to the fish species (Hamza and Selmi, 2018;Ouma, 2020). Wetland trend analysis (depth and area) is very essential for sustainable management planning.…”
mentioning
confidence: 99%